Respuesta :
Step-by-step explanation:
everything can be found in the picture
![Ver imagen nchangcomfort48](https://us-static.z-dn.net/files/d8e/cec8fcb4f56fdec5de71216e2353a6fc.jpg)
Answer:
[tex]\small{\boxed{\tt{2 \sqrt{5} (13 + \sqrt{2} = 26 \sqrt{5} + 2 \sqrt{10} = 64.3}}}[/tex]
Step-by-step explanation:
Given : Expression
[tex]2 \sqrt{5} (13 + \sqrt{2} )[/tex]
To find : Simplify the expression
Solution :
Step 1 - Write the expression
[tex]2 \sqrt{5} (13 + \sqrt{2} )[/tex]
Step 2 - Apply distributive property,
[tex]a(b + c) = a × b + a \times c[/tex]
[tex] = 2 \sqrt{5} \times 13 + 2 \sqrt{5 } \times \sqrt{2} [/tex]
Step 3 - Apply square root property,
[tex] \sqrt{x} \times \sqrt{y} = \sqrt{xy} [/tex]
[tex] = 26 \sqrt{5} + 2 \sqrt{10} [/tex]
or to simplify more substitute the value of [tex] \sqrt{5} = 2.23[/tex] and [tex] \sqrt{10} = 3.16[/tex]
Simplification-
[tex] = 26(2.23) + 2(3.16)[/tex]
[tex]= 57.98 + 6.32[/tex]